Lack of Actor in the State Address of Indonesian President on the 74th Indonesia Independence Day - Jonathan Irene Sartika Dewi Max; Mardliya Pratiwi Zamruddin (Journal of Language and Literature, 2020)
Political speech must be perceived critically in order to avoid the misuse of power. Applying Systemic Functional Linguistics (SFL) and Critical Discourse Analysis (CDA), this paper offered a perspective to understand how power is symbolically exercised through the use of language in Jokowi’s State Address on the occasion of 74th Indonesia Independence Day 2019. The analysis started by collecting the clauses with high modulation represented by the modal word ‘must’. It appeared as the most frequent modal in the speech text indicating that there is an act of commanding given by the President. However, the high modulated clauses did not give a clear guide on who is the liable Actor for the realization of the discourse of an “Advanced Indonesia”. This phenomenon in language was critical to show that there was a possibility of symbolic violence, which happens because of speaker/writer did not clearly state who was the responsible Actor for each specific action required in the discourse of an Advanced Indonesia. In this instance, his speech opens the possibility of symbolic violence. This was proven by 1) the unidentified accountable Actor from the use of the pronoun ‘we’,  2) hidden agent in nominalization in the Material process, 3) the use of passive voice with Material Process, and 4) the process of Relational Process of Attributive used for characterizing Indonesia.